ChemInform Abstract: Synthesis of Boron‐Substituted Diaryliodonium Salts and Selective Transformation into Functionalized Aryl Boronates. Issue 18 (11th April 2013) - Ito, Motoki; Itani, Itsuki; Toyoda, Yosuke; Morimoto, Koji; Dohi, Toshifumi; Kita, Yasuyuki
Abstract The postfunctionalization of aryl boronates using diaryliodonium salts is investigated with a view to the importance of these compounds in organic synthesis.